Comparative analysis of postmortem cerebral ammonia level and Alzheimer type 2 astrocytes with intravital blood laboratory parameters of deceased patients with liver cirrhosis of varying degree - Shulyatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (My University, 2023)
Abstract Purpose - correlation analysis of the postmortem ammonia level and numbers of Alzheimer type 2 astrocytes in different parts of the brain with intravital laboratory blood parameters of deceased patients with liver cirrhosis of varying severity. Material and methods. Autopsied brains of 90 patients with non-alcoholic liver cirrhosis (LC) of class A, B and C according to Child-Pugh formed 3 groups: «A» (n = 30), «B» (n = 30) and «C» (n = 30). Control group - 30 patients deceased from cardiovascular failure. Cortex, white matter, hippocampus, thalamus, striatum and cerebellum were histochemically (HC) studied with Nessler's reagent for ammonia level. Correlation analysis of ammonia expression, Alzheimer type 2 astrocytes (AA2) numbers and 14 intravital laboratory blood parameters was performed. Results. HC method reveals region-dependent ammonia expression in the brain neuropil. The most significant correlations are observed in thalamus, striatum, cerebellum, and cortex between ammonia expression (ACUOD), AA2-astrocytosis, and lifetime values of total bilirubin (for Bil/ACUOD & /AA2 r = 0.31-0.97), AST (for AST/ACUOD & /AA2 r = 0.30-0.81), ALT (for ALT/ACUOD & /AA2 r = 0.30-0.78), leukocyte index of intoxication (for LII/ACUOD & /AA2 r = 0.34-0.76), albumin (for Alb/ACUOD & /AA2 r = -0.34 to -0.78), leukocytes (for Wbc/ACUOD & /AA2 r = 0.31-0.68), prothrombin index (for PI/ACUOD & /AA2 r = -0.31 to -0.45) and potassium (for K+/ACUOD & /AA2 r = -0.32 to -0.45), p <0.05.
Shulyatnikova T. V. - https://orcid.org/0000-0002-0196-9935; Tumanskiy V. O. - https://orcid.org/0000-0001-8267-2350
Keywords: liver cirrhosis; hepatic encephalopathy; ammonia; histochemistry; Alzheimer type 2 astrocytes; blood laboratory parameters